Next generation access networks: the post-investment conundrum - Gonçalves, Ricardo (2016)
Next Generation Access (NGA) networks entails significant investments but brings with it promises of a "brand new world" in telecommunications. In this paper, we provide an overview of some of its implications. In particular, we argue that it is not clear whether the "old" vertical integration model, where network operators provide end-to-end services, is likely to be maintained. But we also argue that, irrespective of that, network operators must look with increased interest at their wholesale revenue stream, i.e., at the possibility that, even if vertically integrated, profits can be reaped from providing access to (potentially rival) retail operators. Moreover, content providers will significantly increase their relevance in the future value chain. Therefore, we argue that revenue sharing mechanisms between content, infrastructure and service providers are likely to (re)emerge.